Evaluasi Soft Skill dalam Pembelajaran Mahasiswa di Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara - Much Imron (Jurnal Dinamika Ekonomi & Bisnis, 2021)
The Faculty of Economics and Business Islamic University of Nahdlatul Ulama Jepara, three years ago has given soft skills training to new students. Therefore, to find out the effectiveness of these activities then need to evaluation student’s soft skill. Evaluation is done by giving questionnaires to respondents that contain statements relating to the attributes of soft skills. Soft skill attributes used in this study include five attributes: critical thinking, creativity, team work, communication skills and time management. The population of this research is 1.287 students of the Faculty of Economics and Business for the year 2015/2016 to 2017/2018, using the Slovin formula with alpha 10%, a sample of 93 students was obtained. Data analysis in this study uses descriptive statistics then the categorization of soft skiil capabilities was carried out.The method of determining the category of students' soft skills is based on the calculation of the highest average with the lowest average. The results of the study show that the five soft skill attributes examined are in the very good category. Students of the 2016 Faculty of Economics and Business have better soft skills than students in 2015 and 2017. Based on existing majors, students majoring in management have better soft skills than accounting and Islamic economics.